Third/Additional Language Learning Strategies in a Globalised World: Learning the Chinese language in Ireland - Li, Qinyuan (Trinity College Dublin. School of Education. Discipline of Education, 2025)
This thesis investigates the language learning strategies (LLS) employed by multilingual learners in Ireland studying Chinese as a third or additional language (L3/AL). Given the growing global importance of Chinese and its rise within Irish education, the research seeks to understand how learners' linguistic backgrounds, proficiency levels, and immersion experiences shape their strategy use. The study focuses on learners from diverse linguistic contexts, particularly those with both English and Irish language proficiency. Adopting a mixed-method approach, the research combines qualitative interviews with quantitative questionnaire data. A total of 14 semi-structured interviews were conducted to explore individual experiences with cognitive, metacognitive, affective, motivational, and social strategies. Additionally, 115 questionnaires were collected to provide a broader understanding of strategy use patterns and their correlation with factors like language background, motivation, and immersion. Key findings reveal that multilingual learners in Ireland use moderate level of LLS when learning Chinese as a L3/AL, with clear evidence of strategy transfer in the interview data. Of the five LLS dimensions, the motivational dimension yielded the highest mean score, while the social dimension scored the lowest. Learner's proficiency level did not significance influence their LLS use. However, immersive language learning experience were found to negatively correlate with the use of metacognitive and affective strategies, possible reasons were discussed. Additionally, individual differences, such as age, gender, and language background also impact LLS use. Notably, high motivation emerged as a critical factor in LLS use among multilingual learners, with a positive cycle proposed to explain this relationship. The thesis highlights the importance of affective and motivational strategies, advocating for learner-centred pedagogical approaches and tailored support to optimise learner's strategy use. This research contributes to the field of language acquisition by providing new insights into LLS in the context of learning Chinese as an L3 in a multilingual environment, with implications for both theory and teaching practice.
APPROVED